2019
DOI: 10.15671/hjbc.518593
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Gold Nanoparticles using Scytosiphon lomentaria (Brown algae) and Spyridia filamentosa (Red algae) from Kyrenia Region and Evaluation of their Antimicrobial and Antioxidant Activity

Abstract: B u çalışma, Scytosiphon lomentaria (kahverengi yosun) ve Spyridia filamentosa (kırmızı yosun) kullanılarak altın nanopartiküllerinin (AuNPs) sentezi için yürütülmüş ve bu iki türden kullanılarak sentezlenen naopartiküllerin karşılaştırması yapılmıştır. Altın nanoparçacıklar daha sonra UV-Vis spektrofotometre, FTIR ve Mastersizer kullanılarak karakterize edilmiştir. UV-Vis kullanılarak altın nanopartiküllerin oluşumu 540 nm'de oluşan pik ile görülmektedir. FTIR'daki gerilme, deniz yosunu ekstraktında bulunan b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 44 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Some leaves and stem bark extracts used in the synthesis of ZnO NPs include Costus pictus D. Don [9], Parthenium hysterophorus L. [10], and A. lebbeck [11]. Studies report bio-extract-mediated ZnO nanoparticles with exclusive properties revealed novel alternatives to cancer therapy, anti-diabetic, antioxidant, and anti-microbial activity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some leaves and stem bark extracts used in the synthesis of ZnO NPs include Costus pictus D. Don [9], Parthenium hysterophorus L. [10], and A. lebbeck [11]. Studies report bio-extract-mediated ZnO nanoparticles with exclusive properties revealed novel alternatives to cancer therapy, anti-diabetic, antioxidant, and anti-microbial activity [12,13].…”
Section: Introductionmentioning
confidence: 99%